PASAR MODAL SYARIAH DI INDONESIA - Fauzia, Ika Yunia (El-Qist: Journal of Islamic Economics and Business (JIEB), 2011)
The Birth of shariah capital market in Indonesia is a breakthrough, in order to open a new niche on the trading floor. With distinct segmentation, it is expected that local Moslem investors and Middle Eastern investors will be colouring investment growth in it. The existance of sharia capital markets, will also participate in enhancing the development and the growth of national economic because it can strengthen industries and companies financial position. In which industries and companies engaged in efforts dealing with shariah, which can provide a positive contribution to people’s live. However modern economy will rely heavily on strong capital markets, global competitivenes and also good system. And it is expected that sharia capital market in Indonesia could have strong competitivenes so that can develop, deliver profit and benefit for the community of investors, industry sectors and society in general.